CONTINUED CLAVICULAR GROWTH DURING ADOLESCENCE AND EARLY ADULTHOOD. Issue 3 (31st March 2019) - Hughes, Jessica; Newton, Peter; Bastrom, Tracey; Pennock, Andrew
Background: As more adults undergo surgical fixation of clavicle fractures, there is a renewed interest in the management of adolescent fractures. While the medial clavicular physis does not fuse until 23-25 years, literature reports limited residual growth of the clavicle during adolescence. The aim of this study is to evaluate the longitudinal clavicular growth on serial thoracic radiographs in adolescents and young adults. Methods: A review was performed on two cohorts of patients: 1. Scheuermann's Kyphosis patients and 2. A prospectively collected adolescent idiopathic scoliosis registry. Patients, 10-25yrs old, were included if they had serial thoracic radiographs over 5 years with at least 3 serial radiographs capturing the entire length of at least one clavicle. Radiographs were excluded for malrotation. Known surgical implant dimensions were utilized to normalize measurements. The measurements were organized into 3 groups: 12-15yrs, 16-19yrs and =20yrs. The overall growth, the growth per year and the growth percentage per year were calculated for each clavicle. Results: Fifty-seven patients met the inclusion criteria (22 males and 35 female). For male patients, age 12-15yrs, the clavicular growth was 5.2 mm/yr and 4.2%/yr, age 16-19yrs: 3.0 mm/yr or 2.3%/yr and for ages 20-25yrs: 1.7mm/yr or 1.4%/yr. For female patients, 12-15yrs, there was 4.6mm/yr and 3.9%/yr, 16-19yrs: 2.0mm/yr or 1.6%/yr, and for age 20-25yrs: 0.8mm/yr or 0.6%/yr. We were unable to detect an age of terminal growth for either gender because residual growth was still ongoing in most patients of the oldest group. Conclusion/Significance: This study suggests that there is continued growth potential of the clavicle after the age of 18yrs and as such more remodeling potential during adolescence than may have otherwise been appreciated. It is unclear how this data will influence surgical decision making in clavicle fracture treatment.